2006
DOI: 10.1177/0361198106195300107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Land Use, Population, Employment, and Economic Activity on Accidents

Abstract: In this study, the relationships between land use, population, employment by sector, economic output, and motor vehicle accidents are explored. Through the use of comprehensive data from the largest county in Hawaii, the relationships are modeled in a uniform 0.1-mi2 (0.259-km2) grid structure and with various linear regression models. This method has an advantage over other approaches that have typically used unevenly sized and shaped traffic analysis zones, census tracts, or block groups. Positive, statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 9 publications
6
16
0
3
Order By: Relevance
“…In particular, workers per residents (WKGD) is associated with C car , C truck , C seg , C peaknight and C day . These results confirm earlier research by Lovegrove et al [15] and Kim et al [39,94]. The difference between C peaknight and C peakday is related to the different activities carried out during the hours of the day.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, workers per residents (WKGD) is associated with C car , C truck , C seg , C peaknight and C day . These results confirm earlier research by Lovegrove et al [15] and Kim et al [39,94]. The difference between C peaknight and C peakday is related to the different activities carried out during the hours of the day.…”
Section: Resultssupporting
confidence: 92%
“…Hbus is a proxy for pedestrian traffic, so the positive sign indicates a growing correlation with crashes. The association between increased collisions and increased bus stops (BS) is consistent with researches of Kim et al [39,94], Wei et al [88] and Rhee et al [98]. A larger number of subway stations were found to increase traffic crashes.…”
Section: Resultssupporting
confidence: 85%
“…Population density contributes significantly to the number of crashes caused by drivers aged between 24 and 64. These results confirm the results of previous studies [24,31,35,43], except for Dumbaugh and Rae [33], who found that population density had a negative effect on the number of injury crashes. The number of household-occupied housing units has a positive and significant impact on crashes by young drivers.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, we adopted a negative binomial model to control for the problems of overdispersion (presence of greater variability) or under dispersion (presence of less variability) based on the observed variance. This model was the preferred approach used in other crash frequency studies [24,25,[30][31][32][33][34][35][36][37][38]. The Poisson model proved inadequate, but the negative binomial model proved to be appropriate.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Consistent with previous studies, pedestrian collision rates were nearly doubled in locations with marked crosswalks (Koepsell et al 2002, Zegeer et al 2005, Mitman et al 2008). Locations in areas that likely have higher pedestrian activity due to more businesses (i.e., higher employment and fast food density), higher residential density, and more bus use had higher pedestrian collision rates, similar to findings in previous studies (Lightstone et al 2001, Kim et al 2006, Miranda-Moreno et al 2011, Moudon et al 2011). Areas with higher proportions of non-Hispanic blacks or other races also experienced higher collision rates, which may be the result of greater pedestrian activity in these neighborhoods (Cottrill and Thakuriah 2010).…”
Section: Discussionsupporting
confidence: 86%